2020
DOI: 10.3390/cells9071717
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: Agents of the CNS Pro-Inflammatory Response

Abstract: The pro-inflammatory immune response driven by microglia is a key contributor to the pathogenesis of several neurodegenerative diseases. Though the research of microglia spans over a century, the last two decades have increased our understanding exponentially. Here, we discuss the phenotypic transformation from homeostatic microglia towards reactive microglia, initiated by specific ligand binding to pattern recognition receptors including toll-like receptor-4 (TLR4) or triggering receptors expressed on myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(162 citation statements)
references
References 413 publications
(529 reference statements)
2
136
0
Order By: Relevance
“…BST2 (CD317) is associated with inactivated microglia [24] and diminishes the expression of inflammatory genes [25]; therefore, BST2 was selected to identify the co-expressed genes associated with inactivated microglia. The phenotypic transformation from homeostatic microglia towards reactive microglia in dementia pathologies is associated with TREM2 [26], HLA-DRA [27], ENTPD1 (CD39) [28], CD80 (B7-1) [29], CD86 (B7-2) [10], CCR5 [30], CD274 [31], ITGAX (CD11c) [32], TIMD4 [33] and MRC1 [34]. Therefore, these candidates were used in the deconvolution analysis to identify co-expressed genes associated with active microglia in "pre-lesions" and PVL.…”
Section: Discussionmentioning
confidence: 99%
“…BST2 (CD317) is associated with inactivated microglia [24] and diminishes the expression of inflammatory genes [25]; therefore, BST2 was selected to identify the co-expressed genes associated with inactivated microglia. The phenotypic transformation from homeostatic microglia towards reactive microglia in dementia pathologies is associated with TREM2 [26], HLA-DRA [27], ENTPD1 (CD39) [28], CD80 (B7-1) [29], CD86 (B7-2) [10], CCR5 [30], CD274 [31], ITGAX (CD11c) [32], TIMD4 [33] and MRC1 [34]. Therefore, these candidates were used in the deconvolution analysis to identify co-expressed genes associated with active microglia in "pre-lesions" and PVL.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivated microglial cells create a neuroin ammatory microenvironment by releasing various proin ammatory factors, thereby ultimately contributing to neurodegenerative progression [44]. Many studies have demonstrated that inhibition of microglial activation by anti-in ammatory compounds or modulation of the expression of some genes attenuated neuronal cell injuries under neurodegenerative conditions, suggesting that suppression of microglial activation may be considered a potential therapeutic approach to neurodegenerative diseases [45][46][47]. In the present study, we found that the glycolytic inhibitor 2-DG signi cantly inhibited neuronal cell death induced by conditioned media from activated microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation can be subdivided into M1 and M2 states. M1 microglia, which are pro-inflammatory cells, release inflammatory molecules such as ROS, RNS, and pro-inflammatory cytokines, and upregulate antigen proteins such as major histocompatibility complex class II [ 4 , 23 ]. In contrast, M2 microglia exhibit anti-inflammatory properties including release of anti-inflammatory cytokines such as interleukin 4 (IL-4), IL-10, and transforming growth factor-beta (TGF-β), leading to tissue repair [ 4 , 23 ].…”
Section: Neuroinflammation and Cns Degenerative Diseasesmentioning
confidence: 99%
“…Although various central nervous system (CNS) disorders, particularly CNS degenerative diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), multiple sclerosis (MS), and amyotrophic lateral sclerosis (ALS), have become a bigger burden to individuals, families, and society, the molecular mechanisms and microenvironments of these disorders have not been fully understood. Neuroinflammation, which involves inflammatory cascades in nervous tissues, may be initiated in response to microglia/astrocyte activation, oxidative stress caused by reactive oxygen/nitrogen species (ROS/RNS), and mitochondrial excitotoxicity [ 1 , 2 , 3 , 4 , 5 ]. Sustained and prolonged neuroinflammation can result in persistent and chronic apoptotic neuronal cell death and programmed cell death (pyroptosis and necroptosis), thereby triggering various CNS degenerative disorders [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%